The Phenomenon of Transgenerational Links of Generations - Sargsyan, Syuzan (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
Genetic memory is the ability to remember what we should not remember, which was not in the direct experiences. Genetic memory sometimes comes up from the subconsciousness and causes unclear images, impressions and feelings. Genetic memory can occur during sleep. Genetic memory enters into the composition of the collective unconsciousness. One of the most significant phenomena of genetic memory – transgenerational transmission, does not fully resolve the conflict, mystery, the experience of injustice, which is passed on to the unconscious child from the unconscious parent, from generation to generation.